-12=18z+12

Simple and best practice solution for -12=18z+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12=18z+12 equation:


Simplifying
-12 = 18z + 12

Reorder the terms:
-12 = 12 + 18z

Solving
-12 = 12 + 18z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-18z' to each side of the equation.
-12 + -18z = 12 + 18z + -18z

Combine like terms: 18z + -18z = 0
-12 + -18z = 12 + 0
-12 + -18z = 12

Add '12' to each side of the equation.
-12 + 12 + -18z = 12 + 12

Combine like terms: -12 + 12 = 0
0 + -18z = 12 + 12
-18z = 12 + 12

Combine like terms: 12 + 12 = 24
-18z = 24

Divide each side by '-18'.
z = -1.333333333

Simplifying
z = -1.333333333

See similar equations:

| 10(-4+x)=2x | | 0.25x-3.4=0.15x-7.3 | | 15x^3-3x^2+10x-2=0 | | 2+r=-2 | | 24-7x=-36+5x | | 0.05u+27.5=0.6-11 | | 67-2x+6=5x-2 | | 10=-2x+22 | | 3(x-45)+2x=540 | | -9+4r=-3-6 | | 4x+2=4x+6 | | 11x^2+2x+24=0 | | -10w+3=52 | | 67-(2x+6)=5x-2 | | 8(7y+6z)-48z= | | 15=-3n | | 9x+84=28x | | 12g=-108 | | -4x-14=6-2x | | 3x-2(3+x)=9 | | 7(x-5)=-7(x+5) | | 10a^4b-25a^3b+15ab=0 | | 0.5(4a+10B)=C | | (x^2+3)+(4+2x)=15 | | -6=5t+4 | | p/7=21 | | 6x+4=20x+7 | | 11x-8=12+x | | -16m=48 | | 2p^2+3p^2-8p^3-6p^3= | | 6x+4-1=20x+6 | | 3x-2(7-2y)=10 |

Equations solver categories